2009
DOI: 10.1111/j.1468-1293.2009.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antiretroviral prescription patterns and treatment guidelines in treatment‐naïve HIV‐1‐infected patients

Abstract: Reports have shown that the publication of practice guidelines does not guarantee their use in clinical practice. The objective of this study was to evaluate the agreement between antiretroviral treatments (ARTs) prescribed in clinical practice and the recommendations in published guidelines. ResultsA total of 945 patients initiated ART. Of these patients, 12.3% had a CD4 cell count above 350 cells/mL. A 'nonrecommended' antiretroviral regimen was prescribed to 5.3, 5.1 and 7.8% of patients with CD4 counts o2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…We found that the choice of initial antiretroviral regimen was appropriate in most cases: 91.5% of patients started treatment that was considered recommended or alternative by the guidelines. This is consistent with a study in the Spanish Asociación Médica Vach de Estudios Multicéntricos (VACH) cohort in the years 2004–2006, which found that initial treatment regimens were compliant with the guidelines in 95% of cases . Similar proportions have been found in other European studies , but studies from the USA have found lower percentages of compliance .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the choice of initial antiretroviral regimen was appropriate in most cases: 91.5% of patients started treatment that was considered recommended or alternative by the guidelines. This is consistent with a study in the Spanish Asociación Médica Vach de Estudios Multicéntricos (VACH) cohort in the years 2004–2006, which found that initial treatment regimens were compliant with the guidelines in 95% of cases . Similar proportions have been found in other European studies , but studies from the USA have found lower percentages of compliance .…”
Section: Discussionsupporting
confidence: 90%
“…Guidelines for the treatment of HIV infection are available in many countries [3][4][5]; however, there is little evidence assessing compliance with clinical practice guidelines for antiretroviral treatment and its impact on clinical outcomes. Among the few studies that have investigated this issue [6][7][8][9][10][11][12][13][14][15][16][17], only two [7,13] evaluated the relationship of adherence to treatment guidelines with immunovirological outcome. Most importantly, none of these studies has evaluated its relationship with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research of HIV/AIDS clinical trials results showed differences in how quickly trials were completed and subsequently published, affecting the availability of evidence to the broader scientific community (Ioannidis, 1998). Research also shows a strong adherence to the recommendations found in practice guidelines by clinicians for the treatment of HIV/AIDS patients (Suarez-Lozano et al, 2009; Petersen et al, 2011), emphasizing the importance of the use of secondary research outputs in the field. These prior studies suggest the need to operationalize patterns of recognition over time as a way to more precisely assess the movement from clinical trial results to changes in clinical practice.…”
Section: Introductionmentioning
confidence: 74%
“…Publication of practice guidelines does not guarantee their use in clinical practice. Routine evaluation of adherence to guidelines has thus been recommended as a measure of quality of care (Suarez-Lozano et al 2009). In several low-income countries guidelines are changing or have changed already.…”
Section: Introductionmentioning
confidence: 99%